EVIDENCE OF PRECURSOR PHENOMENA IN THE KOBE EARTHQUAKE OBTAINED FROM ATMOSPHERIC RADON CONCENTRATION - Yasuoka Y.; Shinogi M.; Igarashi G.; Ishikawa T.; Tokonami S. (My University, 2006)
Atmospheric 222Rn concentrations were determined over a 10a period, which included the date of the Kobe, Japan earthquake, on January 17th 1995. It was found that the seismically related 222Rn anomaly was higher than the 99% confidence limits for the residual value of atmospheric 222Rn which had been observed 2 months before. The residual 222Rn concentration, in which residual values of the daily minimum are the difference between each normal 222Rn concentration (calculated from January 1984 to December 1993) and the daily minimum 222Rn concentration (January 1994 to January 1995), was calculated by applying the exponential smoothing method to the residual values for each day. It was found that the fluctuations of the residual values can be fitted very well to a log-periodic oscillation model. The real residual values stopped increasing at 1994.999 (December 31st 1994), which corresponds with the critical point (tc) of best fit model. This anomalous 222Rn variation can be seen as the result of local stresses, not primary stresses which directly lead to the Kobe earthquake. On the other hand, when the critical exponent (z) and the radial frequency (ω) of the model were simultaneously fixed 0.2 {less-than or slanted equal to} z {less-than or slanted equal to} 0.6 and 6 {less-than or slanted equal to} ω {less-than or slanted equal to} 12, tc (critical point) was between January 13th 1995 and January 27th 1995. The Kobe earthquake occurrence date (January 17th 1995) is within this range. Therefore this anomalous 222Rn variation can also be seen as the result of primary stresses which possibly led to the Kobe earthquake. There is a distinct possibility that similar statistical oscillations will be detected in other measurements such as microseismicity, tectonic strain, fluctuation in the ground level, or changes in groundwater elevations and composition. © 2006 Elsevier Ltd. All rights reserved.